PENDAMPINGAN MENGGUNAKAN STRATEGI TUGAS MENGENAL MASALAH UNTUK MENINGKATKAN KEMAMPUAN MENYUSUN PROPOSAL PTK BAGI GURU BINAAN KOTA PALU - DORCE LIMBONG LEBOK (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
Since the launch of one of the promotion requirements for the teaching profession, namely Scientific Writing, especially Classroom Action Research (PTK), it turns out that up to now there are still many teachers who do not understand conducting Classroom Action Research and compiling PTK results reports. Sensing this condition, the researchers provided assistance to trained teachers at Palu City Middle Schools. Mentoring uses the Problem Recognition Task strategy. The research subjects were Christian Religious Education teachers as trained teachers in the researcher's supervision area. The research design is collaborative School Action Research (PTS). The research was conducted in two cycles. Data collection techniques use written tests and observations. Data analysis was carried out descriptively, quantitatively and qualitatively. The results of the analysis for the implementation of the RPP in cycle I obtained a score of 102 (85%) qualitatively in the category